Utility of optical coherence tomography in the evaluation of sellar and parasellar mass lesions. Issue 4 (August 2018) - Al-Louzi, Omar; Prasad, Sashank; Mallery, Robert M.
Abstract : Purpose of review: Anterior visual pathway compression is a common feature of sellar region masses. We review the visual pathway neuroanatomy pertaining to sellar and parasellar lesions and describe recent advances in optical coherence tomography (OCT) imaging that have provided a novel quantitative perspective in the evaluation and management of such patients. Recent findings: Ultrastructural measurements of optic nerve integrity using OCT, namely peripapillary retinal nerve fiber layer (pRNFL) and the ganglion cell and inner plexiform layer (GCIPL) thicknesses, have been shown to correlate with visual acuity and visual field deficits on perimetry in patients with compressive sellar region masses. In some cases, OCT can visualize early signs of anterior visual pathway involvement in the absence of clinically evident visual field loss or optic disc pallor. OCT is particularly useful when assessing patients who demonstrate less reliable visual field testing. Furthermore, there is growing awareness that pRNFL and GCIPL thinning preoperatively correlate with worse visual recovery following chiasmal decompression, highlighting the prognostic utility of OCT in this patient population. Summary: OCT provides a complimentary, yet critical, role in quantitatively assessing ultrastructural retinal injury in patients with sellar and parasellar lesions compressing the anterior visual pathway and should be incorporated into routine evaluation.